POLITIK HUKUM NEGARA DALAM PENCEGAHAN PERCERAIAN DI INDONESIA MELALUI BADAN PENASIHATAN PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) - Aulia Isnaini Dahlan; Firdaus Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
As a legal state, Indonesia has a Marriage Law which adheres to theprinciple of making divorce difficult. Divorce is regulated in Law no. 1 of 1974concerning Marriage as amended by Law no. 16 of 2019. Divorce only occurs ifcertain reasons are fulfilled in the legislation and are carried out before the court.This relates to the principle of complicating divorce in order to prevent someone fromtaking divorce steps. Even though this law has been implemented, it cannot be deniedthat currently the number of divorces that occur in society every year continues toincrease.Efforts to prevent divorce are also carried out by the government, through theBadan Penasihatan Pembinaan dan Pelestarian Perkawinan (hereinafter referred toas BP4) which is a partner organization of the Ministry of Religion which is engagedin providing advice on marriage, disputes and divorce. Then there was arevitalization of BP4 through the 14th BP4 National Conference in 2009 which wasoriginally only a consulting institution on marriage issues, through this NationalConference it expanded its duties not only as an extension institution, but also hadmore comprehensive tasks, including providing mediation assistance to parties wholitigation in the Religious Courts. However, it is unfortunate that this change does notcoincide with strengthening the legal basis of an adequate institution and tends toexperience a decline in legal authority. Previously, BP4 had a legal basis through theDecree of the Minister of Religion No. 85 of 1961, which was changed to the Decreeof the 14th BP4 National Deliberation No. 26/2-P/BP4/VI/2009 concerning theArticles of Association of BP4.This research was conducted using normative juridical research studies,namely research conducted by examining secondary legal materials that havesomething to do with the material of this thesis. From the research results there aretwo main things that can be concluded. First, a stronger BP4 institutional legal basisis needed through law. So that BP4 has greater authority in terms of carrying out itsduties and functions related to efforts to prevent divorce. Second, also in terms ofstrengthening legal substance, namely strengthening the legal basis of BP4institutions through laws, strengthening legal structures, namely regulations that alsohelp strengthen and assist performance in efforts to prevent divorce from BP4 itself.And finally strengthening the legal culture, namely people's attitudes towards the lawand the legal system, which is related to beliefs in their values, thoughts or ideas. Theimportance of a legal culture that is in harmony with society so as to createinstitutions that are in accordance with the culture of Indonesian society in efforts toprevent divorce itself.Keywords : State Law Politics, Divorce Prevention, and BP4.